Structure-subsoil contact task - an iterative engineering realisation - Fedorowicz, Lidia; Fedorowicz, Jan (Computer Assisted Methods in Engineering and Science, 2000)
The analytical formulation of an iterative procedure applied for structure- subsoil systems is presented in the paper. A physical and engineering interpretation has been given for the presented algorithm.